What factors influence thriving in adolescent and young adult cancer patients? A focus on psychological health, biological markers, and quality of life - Yi Zhou; Yinglong Duan; Jian Zhou; Qinqin Cheng; Ning Qin; Xing Zhou; Yuxuan Li; Juan Luo; Huiyi Zhang; Jiayi Zhu; Jianfei Xie; Andy S. K. Cheng (BMC Psychology)
Abstract Purpose This study explores the role of psychological health, biological markers, and quality of life (QoL) in influencing thriving - defined as resilience and enhanced well-being - among adolescent and young adult (AYA) cancer patients. Methods A total of 148 AYA cancer patients were assessed for psychological health indicators (anxiety, depression, character strengths), physiological markers (cortisol awakening response [CAR], melatonin), and QoL. Thriving levels were evaluated using ordinary least squares regression and quantile regression to identify predictors across different thriving percentiles. Results Psychological health was the strongest predictor of thriving. Depression negatively impacted thriving at lower levels, while inquisitiveness consistently enhanced it. CAR and melatonin played roles at higher and median thriving levels, respectively, and QoL was most influential at lower levels. These factors collectively explained 23.0% of the variance in thriving scores. Conclusions This study highlights depression, inquisitiveness, CAR, and QoL as key factors influencing thriving in AYA cancer patients. Depression affects thriving at lower levels, inquisitiveness enhances thriving consistently, CAR is significant at higher levels, and QoL is crucial at lower levels. These findings underscore the need for tailored interventions to support thriving across varying levels of adaptation.